Nejstarsi data o narodnosti v nasich zemich - Sekera, V (Demografie, 1981)
The author discusses the beginning of the systematic collection of data on nationalities and linguistic groups in Czechoslovakia during the eighteenth century. The collection of this type of data was a result of two factors: the need for topographic data by secular and ecclesiastic authorities and the general growth of scientific research. The different types of data collected are also examined. Topographic materials generally dealt with the ethnicity of individual places, while scientific studies focused on global data on nationalities.
Keywords: Developed Countries; Demography; Europe, Eastern; Historical Survey; Research; vyspělé země; zeměpis; sběr dat; východní Evropa; populace; populační charakteristiky; Population Characteristics; Geography; jazyk (prostředek komunikace); výzkum; Research Methodology; Ethnicity; Population; Europe; Data Collection; Ethnic Groups; Eastern Europe; kultura; Language; Československo; Communication; Demographic Factors; Czechoslovakia; demografie; komunikace; etnicita; Cultural Background; Geographic Factors; Culture; Evropa